Integrating Traditional Medicine to Achieve Universal Health Coverage: A Scoping Review - Dwi Retno Murdiyanti; Chriswardani Suryawati; Cahya Tri Purnami (Indonesian Journal of Global Health Research, 2024)
One way to maintain health is by using traditional medicine. WHO recommends that traditional medicine be integrated into health care systems to achieve universal health coverage, but most countries have not adopted the recommendation. In this study, we will observe the implementation of the integration of traditional medicine in the health service system that supports universal health coverage. In this study, a scoping review was carried out by searching for articles from the Pubmed and Scopus databases with appropriate keywords, in English that can be fully accessed by Diponegoro University students from 2013 - 2024. The result, 39 journals were obtained from Scopus and Pubmed which were then screened with inclusion and exclusion criteria. From the screening process, 3 journals were obtained that were suitable for the integration of traditional medicine in the health service system to support the achievement of universal health coverage. Conclusion: The government needs to regulate the use of traditional medicine in the health service system based on scientific evidence, carried out by competent personnel, standardization of product and service quality, service evaluation, continuing education to achieve universal health coverage.